Diskursus Pemberitaan Media Online mengenai Penerimaan Izin Usaha Pertambangan oleh Muhammadiyah dan Nahdlatul Ulama - Romadlan, Said; Maududi, Mukhlish Muhammad; Wahdiyati, Dini; Putra, Gilang Kumari (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
As an Islamic community organization, Muhammadiyah and Nahdlatul Ulama (NU) have received an offer for a mining business license from the Government. This acceptance raises pros and cons from various circles.The controversy over the receipt of mining business licenses by Muhammadiyah and NU then became a discourse in the online media, where there was a discourse of pros and cons over the receipt of the mining permit. This study aims to show the discourse of online media news regarding the receipt of mining business licenses by Muhammadiyah and NU. For this reason, the method used is the discourse analysis of the Halliday-Hasan model which focuses its analysis on three elements, namely (1) tenor of discourse, (2) field of discourse, and (3) mode of discourse. The results of the study show that there are two areas of discourse that appear in the online media, namely approving (pro) and rejecting (con) the receipt of mining business licenses by Muhammadiyah and NU. For the tenor of discourse in the field of discourse who agree are dominated by sources from Muhammadiyah leaders, NU leaders, and members of the House of Representatives. Meanwhile, the tenor of the discourse who refused came from Muhammadiyah internal circles, non-governmental organization activists, academics/experts, and members of the House of Representatives. The mode of discourse used by online media are descriptive, argumentative, and persuasive writing styles. The results of this study strengthen the influence of media routines on the practice of media discourse.